Level of service (LOS) for multilane highway and road accident information system development of Batu Pahat area - Abdullah, Mohd Ezree (2005)
In recent years, the advance of Database Management System (DBMS) and Software Tools as an information system which can store and analyses various types of data efficiently had prompted many users to exploit its advantages for their respective fields. In Malaysia, the original products of DBMS and Software Tools have been widely used in fields like urban planning, land management and property valuation. As for traffic engineering users, it is still at the beginning stage. Therefore, to enhance this technology into the traffic engineering fields, the Level of Service (LOS) for Multilane Highway and Road Accident Information System (LORIS) is developed. The main function of LORIS is to analyse LOS which is very important issue for traffic engineer because it describes the traffic operational conditions within a traffic stream. Besides that, road accident data and basic highway information was also included in this system. In this study, the potential of using this system in traffic and accident analysis were conducted only at Batu Pahat area, which is among the highest road accident rate in Malaysia. The objectives are to develop a database and information system to determine the LOS, road accident information and basic highway information. To achieve this, Microsoft Access 2003 was utilised incorporating with Microsoft Visual Basic 6.0. As the results, an effective computerised LOS calculation system had been developed together with road accident and highway information system. The system has been calibrated and validated to obtain reliable results.